FAKTOR-FAKTOR YANG MEMENGARUHI FIRM VALUE - Prawira, Antony; Susanto, Liana (Jurnal Paradigma Akuntansi, 2024)
This study aims to obtain empirical evidence about the effect of profitability, leverage, liquidity, and firm size on firm value in manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The number of samples in this study was selected by purposive sampling method and the valid data were 78 companies. The research data were analyzed using multiple linear regression analysis techniques which were processed with Eviews12 SV software. The results of this study indicate that profitability and leverage have a significant positive effect on firm value. Liquidity does not have a significant effect on firm value. Firm size has a significant negative effect on firm value. The implication of this research is the need to increase profitability and leverage to increase firm value which will give a positive signal to investors.